2014
DOI: 10.1530/jme-13-0182
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin increased endothelial ICAM1 by cPLA2-dependent NF-κB and PKA pathways in HUVECs

Abstract: Urocortin (Ucn1), a member of the corticotrophin-releasing hormone (CRH) family, has been reported to participate in inflammation. The increased expression of intercellular adhesion molecule 1 (ICAM1) plays important roles in inflammation and immune responses. Our previous results demonstrated that Ucn1 significantly enhanced the expression of ICAM1. However, the underlying mechanisms are still unknown. The purpose of this study is to investigate the detailed mechanisms of Ucn1-induced upregulation of ICAM1. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Taken together, the present data suggest that visfatin is an influential upstream factor inducing inflammation and the apoptosis of EPCs, and that its activity results in decreased quantities of EPCs via the upregulation of NF-κB. These findings are in line with those of previous studies demonstrating the involvement of NF-κB in endothelial cell dysfunction and impaired angiogenesis ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, the present data suggest that visfatin is an influential upstream factor inducing inflammation and the apoptosis of EPCs, and that its activity results in decreased quantities of EPCs via the upregulation of NF-κB. These findings are in line with those of previous studies demonstrating the involvement of NF-κB in endothelial cell dysfunction and impaired angiogenesis ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…Placental CRH exhibits distinct responses to glucocorticoids and during gestation there is a bi-directional release of pCRH into the maternal and fetal compartments ( 29 , 30 ). Acting via type 1 (CRH-R1) and type 2 (CRH-R2) receptors, CRH coordinating homeostatic challenges ( 31 ) that might be crucial in fetal maturation and providing nutritional signals that ultimately control pace of fetal development. It is thus reasonable to assume, that hormonal imbalances associated with severe or prolonged stress response, could potentially affect optimal outcomes ( 18 ).…”
Section: Adaptation To Maternal Stress Resilience and Neurodevelopmentmentioning
confidence: 99%
“…Our previous work showed that UCN up-regulated cPLA2 expression via CRFR1 and down-regulated iPLA2 expression via CRFR2 [18]. In HUVECs, UCN time-dependently increased cPLA2 expression and activity via both CRFR1 and CRFR2 [19]. Similarly, both CRF and UCN increased cPLA2 expression in cultured human placental trophoblasts [36].…”
Section: Discussionmentioning
confidence: 95%
“…urocortin (UCN) was observed to increase cPLA2 expression to promote cell migration by CRFR1, whereas it decreased iPLA2 expression to suppress cell migration by CRFR2 in hepatic cancer cells [18]. In human umbilical vein endothelial cells (HUVECs), UCN increased cPLA2 expression and phosphorylation [19]. Taken together, it is reasonable to speculate a link between CRF system and S1P in the regulation of PLA2.…”
Section: Introductionmentioning
confidence: 97%